2016
DOI: 10.4103/2249-4863.197281
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity correlates of overweight and obesity in school-going children of Dehradun, Uttarakhand

Abstract: Background:Physical activity is important for prevention of overweight and obesity in growing children.Objective:The present study aims to explore the association of overweight and obesity in school children of the district of Dehradun with physical activity, sports, and recreation at home and school.Materials and Methods:A cross-sectional survey of 1266 schoolchildren of select private and government schools in urban and rural areas was done.Results:Overall 15.6% of children were overweight, of which 5.4% wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…In a cross sectional study conducted by Madhavi et al in 1266 school children in Dehradun, Uttarakhand (2013), it was found that 15.6% of the children were over weight of which 5.4% were obese. 11 Also in a study was conducted by MahaNubani-Husseini et al, the prevalence of overweight and obesity was 22.2% and 7.6% respectively, with private schools having the highest rates with 29.6% and 12.8% respectively (p=0.001). 6 In the present study 28.7% were pre-obese and 1.9% were obese in private schools.…”
Section: Discussionmentioning
confidence: 91%
“…In a cross sectional study conducted by Madhavi et al in 1266 school children in Dehradun, Uttarakhand (2013), it was found that 15.6% of the children were over weight of which 5.4% were obese. 11 Also in a study was conducted by MahaNubani-Husseini et al, the prevalence of overweight and obesity was 22.2% and 7.6% respectively, with private schools having the highest rates with 29.6% and 12.8% respectively (p=0.001). 6 In the present study 28.7% were pre-obese and 1.9% were obese in private schools.…”
Section: Discussionmentioning
confidence: 91%
“…A Dehradun based study by Bhargava et al in the year 2013 found a significant association between the lack of physical activity and overweight and obesity in school-going children. 13…”
Section: Discussionmentioning
confidence: 99%
“…Private school students spent very little time in household work, but this did not appear to translate into additional time for active recreation. In a recent qualitative study, private school students in New Delhi discussed their academic workload as one of the most significant barriers to PA (Satija et al, 2018), and Bhargava et al (2016) found that private schools in the northern Indian state of Uttarakhand were well-equipped with sports materials and structured play areas, but allotted little time for PA. As of 2019, India’s Central Board of Secondary Education (CBSE) requires all schools to implement a daily 60-minute physical education period for students in Grades 1 to 12 (ages 5–18). However, the CBSE does not regulate all schools in the country and implementation and enforcement vary widely (Bhawra et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Still, school type is not only an indicator of household socioeconomic status; some poorer families send children to private school as an investment in future financial prospects. School type also indicates exposure to varying social and material supports for PA. For example, although private schools commonly provide greater access to sports equipment and play areas, a strict focus on academics may prevent extensive use of these resources (Bhargava et al, 2016). In contrast, although public school students may have fewer material supports for PA, they may be allowed more unstructured play time during school hours (Bhargava et al, 2016).…”
mentioning
confidence: 99%